2019
DOI: 10.5021/ad.2019.31.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Different Cosmetic Habits Can Affect the Biophysical Profile of Facial Skin: A Study of Korean and Chinese Women

Abstract: Background: Previous studies on the age-, climate, and skin care habit-related changes of biophysical parameters have mainly focused on Caucasians, and studies on Asians are in paucity. Objective: This study was aimed to investigate the variations of cutaneous biophysical parameters in Chinese and Korean women (northeast Asians) and to assess the association between those parameters and age, climate, and cosmetic habits. Methods: A cross-sectional study included 361 healthy Chinese and Korean women between 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…35 Several studies identified no association between TEWL and age. 16,18,27 However, a negative correlation of TEWL with age has been revealed by other researchers. 5,9,30 Discrepancies in the measured region selection, age groupings, race and geographical location might explain these conflicting results.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…35 Several studies identified no association between TEWL and age. 16,18,27 However, a negative correlation of TEWL with age has been revealed by other researchers. 5,9,30 Discrepancies in the measured region selection, age groupings, race and geographical location might explain these conflicting results.…”
Section: Discussionmentioning
confidence: 82%
“…26 According to the available literature, the regional differences of the sebum content are consistent with our results. 9,16,18,27 The lowest sebum level which was found for the cheek might contribute to the increased pH there, since epidermal lipids exist as non-ionic acid or in the ionic form depending on the pH. 28 In most studies, researchers considered that the various skin parameters and age were linearly correlated, and linear regression or linear correlation coefficient was used to describe the situation.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that the skin Fitzpatrick’s classification of Chinese women ranged from type I to type IV, with more types II and III in this study. This may be related to the fact that women have paid more attention to sun protection in recent years ( 27 , 28 ). Pigmentary changes in Asians are more obvious problems relative to the earlier occurrence of wrinkles in Caucasians ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sebum, porphyrin count, pore count, yellowing and TEWL are related to the second PC, independent from the first PC including skin brightness and uniformity. Considering that sebum decreases and yellowing increases with age in an independent mechanism of that of the skin uniformity, it is reasonable that these features contribute to the second PC [17][18][19][20]. In particular, sebaceous glands, organs that secrete sebum, open into pores, and it is highly plausible that the relationship between pores and sebum is captured.…”
Section: Discussionmentioning
confidence: 99%